2014
DOI: 10.1371/journal.pone.0111078
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life GOLD 2011 Implementation: The Management of COPD Lacks Correct Classification and Adequate Treatment

Abstract: Chronic obstructive pulmonary disease (COPD) is a serious, yet preventable and treatable, disease. The success of its treatment relies largely on the proper implementation of recommendations, such as the recently released Global Strategy for Diagnosis, Management, and Prevention of COPD (GOLD 2011, of late December 2011). The primary objective of this study was to examine the extent to which GOLD 2011 is being used correctly among Czech respiratory specialists, in particular with regard to the correct classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
(40 reference statements)
1
12
0
Order By: Relevance
“… 19 Nishimura et al suggested that only 14% of COPD patients were treated with ICS in Japan when asthma was clinically excluded. 20 Percentages of patients on ICS therapy were 34%, 69%, 60%, and 50% in the present, Wurst’s, 13 Price’s, 14 and Koblizek’s 15 studies, respectively. Frequencies of concomitant asthma were 20%, 44%, 28%, and 0%, respectively, in the four studies, ie, patients with asthma were excluded in Koblizek’s study.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“… 19 Nishimura et al suggested that only 14% of COPD patients were treated with ICS in Japan when asthma was clinically excluded. 20 Percentages of patients on ICS therapy were 34%, 69%, 60%, and 50% in the present, Wurst’s, 13 Price’s, 14 and Koblizek’s 15 studies, respectively. Frequencies of concomitant asthma were 20%, 44%, 28%, and 0%, respectively, in the four studies, ie, patients with asthma were excluded in Koblizek’s study.…”
Section: Discussionmentioning
confidence: 48%
“…Koblizek et al reported that despite the high awareness of the GOLD 2011 strategy among Czech COPD specialists, its real-life implementation was rather insufficient. 15 They claimed that 15.5% of COPD patients received ICS unnecessarily, and in 12.2% of cases, ICS was omitted contrary to the guideline recommendations. Among the COPD subjects enrolled in the COPDGene Study, subjects who were on triple therapy had the highest frequencies of exacerbations and severe exacerbations compared to others.…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation of 1355 patients with COPD in the Czech Republic indicated that 32.8% of cases were misclassified according to GOLD categories. Furthermore, 15.4% of patients received ICS unnecessarily, whereas in 15.8% of cases ICS were erroneously omitted [ 75 ]. In a French cohort study, ICS were prescribed outside their indications in ∼75% of patients if the “old” GOLD guidelines were taken as the reference, and in one-third when considering the new GOLD document [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to a study from the United Kingdom, in which 38% of GOLD stage I or II COPD patients were overprescribed ICS. 6 Recently, a study conducted by Koblizek et al 7 in the Czech Republic also found that 19.5% of COPD patients were overprescribed ICS.…”
Section: Discussionmentioning
confidence: 99%